A Case Report of Gastric Squamous Cell Carcinoma Associated with Pancreatic Adenocarcinoma and Literature Review - Shiwei Yao; Xueyong Deng (Case Reports in Gastroenterology)
Introduction: It is common for advanced pancreatic adenocarcinoma to infiltrate the gastric wall, and the tumor cells invading the gastric wall are usually consistent with pancreatic adenocarcinoma. However, it is very rare for the tumor cells infiltrating the gastric wall to be squamous cell carcinoma. Case Presentation: In this case, we report a 57-year-old man who presented with weight loss for 2 months. CT revealed a pancreatic mass. Endoscopic ultrasound biopsy of the pancreatic mass confirmed pancreatic adenocarcinoma. He refused treatment. Eight months later, he developed melena. CT revealed that the pancreatic mass had invaded the gastric wall. Gastric squamous cell carcinoma was confirmed by biopsy of gastric tissue under gastroscopy. Conclusion: By observing the evolution process of this case, we found that the occurrence of gastric squamous cell carcinoma in this case was consistent with one of its pathogenesis: the theory of adenocarcinoma differentiating into squamous cell carcinoma. It provides certain clinical significance for the study of the mechanism of gastric squamous cell carcinoma.